Technical and energy evaluation of municipal solid waste in Sogamoso–Boyacá-Colombia. (2023)
Municipal solid waste (MSW) is the waste generated by the city population, a product of residential, institutional and commercial activities in each municipality. It is considered garbage and is taken to a landfill for its final disposition Its composition is diverse, organic and inorganic waste, microorganisms among others. Waste with inorganic composition mostly has energy properties measured through its heat capacity; this property is of great importance to be used in Waste to Energy (WTE) processes. In Colombia there is still no successful case of implementation of waste-to-energy conversion technologies and feasibility will depend on the regional context in addition to the particularities of the market. This work shows a specific case study through a technical evaluation of the potential use as an energy source of the MSW received in the Terrazas del Porvenir landfill in Sogamoso. The results showed that the recovery of only 42.3% of this waste has an approximate energy potential of 628 TJ/year, which contributes to the supply of energy demand in the region's industries and the possible substitution of fossil fuels such as coal, in addition to the positive contribution to reducing the environmental impact and increasing the useful life of the landfill located in Sogamoso by 5 years.